EFFECT OF TEMPERATURE AND GERMINATION MEDIA ON A VIABILITY OF POLLEN GRAIN OF FIVE PISTACHIO MALE STRAINS - Mohamad Kardoush (Mesopotamia Journal of Agriculture)
This experiment was conducted to evaluate the effect of germination media and three temperatures on five male strains of pistachio at research center of agriculture faculty – Aleppo,(Arab center),.In this experiment, the rates of pollen germination were tested in different germination media (sucrose 10%, sucrose 10%+0.25 gr. boric acid P L. and sucrose 10%+0.0625 gr. boric acid P L.) with 3 temperature levels( 10,20 and 30◦c) .The media was contain 3 gr. agar per liter of water. The results showed that male strain 36 was gave the best germination rate, (78.33 % and tube length 796.1micron) as compared with other strains ,and male strain 47 was the lower (63.11%,511.3 micron) tube germination and tube length (63.11%,511.3 micron) respectively, but all were gave high rates of germination. sucrose 10% media gave the best germination rate (77.07%) and sucrose 10%+ 0.25 gr. boric acid P L. gave the lowest germination rate (62.2%), sucrose 10%+0. 0.25 gr. boric acid P L. gave highest tube germination length (777.68micron), where as 10% sucrose +0.0 625gr. boric acid P L. was the lowest tube length (499.88micron) .On the other hand, 30◦c gave the best germination rate and pollen tube germination length (88.73%and 1005.26 micron), however 10◦c gave lowest rates of these parameters (45.53% and, 244.3 micron) for germination rate and tube pollen length respectively. Generally, all media were gave highest significant results in germination rates and pollen tube length for all strains at all temperatures. we conclude that sucrose 10%was better media for pollen germination and sucrose 10%+0. 25 gr. boric acid P L.was the best for pollen tube length .